School Leadership Support Towards Teachers' Management of Students’ Discipline in Uganda Secondary Schools in the Post Corporal Punishment Era-Northern Region - Santo, Ocii; Eduan, Wilson; Eduan, Amero Stella (East African Journal of Education Studies, 2025)
The study explored leadership measures provided by schools’ head teachers towards teachers' management of students’ discipline in Uganda secondary schools. It adopted two qualitative data collection methods: semi-structured in-depth interviews and document review. Interviews were conducted with 4 head teachers focusing on their leadership support toward discipline management. One-on-one interviews allowed for deeper insights into the topic. Documents review included school policy, training programme for teachers, log books and disciplinary records providing how teachers were supported in managing learners’ discipline. Purposive sampling of four schools was done based on the recommendations from the schools’ inspectors’ report. Data was thematically analysed by grouping it into themes and further assigned codes. To ensure the credibility of the instruments, consistency checks were done throughout the process of coding, transcription, and putting into themes while the instrument’s trustworthiness was assessed by pre-testing the instrument questions in 2 schools. The finding indicated that discipline is defined as a system, and these systems are managed through procedures such as discipline code, consultation, guidance, and counselling to modify inappropriate behaviours, provide effective communication, and make school safe by providing a conducive healthy environment. The study recommends that school educators usher disciplinary problems with empathy for the possible problems students may be experiencing at school that cause their indiscipline. This necessitates the use of alternative discipline approaches in schools. Therefore, school teachers should all be taught alternative approaches to school discipline, such as guidance and counselling, to make the school a safe learning environment